2003
DOI: 10.1088/0022-3727/36/10a/310
|View full text |Cite
|
Sign up to set email alerts
|

Full three-dimensional modelling of curvature-dependent snow metamorphism: first results and comparison with experimental tomographic data

Abstract: Snow, from its fall until its full melting, undergoes a structure metamorphism governed by temperature and humidity fields. Among the many possible mechanisms that contribute to snow metamorphism, those that depend only on curvature are the most accessible to modelling. The isothermal metamorphism of a dry snow sample near 0˚C is addressed in this paper. Near 0˚C, the vapour pressure of water is high: the metamorphism can be considered, in first approximation, as fully curvature-driven. This corresponds to neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 16 publications
3
111
0
Order By: Relevance
“…The real part is that of Warren and Brandt (2008). For the imaginary part, Gosse et al (1995) recommend 4.26×10 −4 at −22 • C, with an error of 3% and a temperature dependence of 0.6% K −1 (Warren and Brandt, 2008), so that our value is within the acceptable range. The effect of using modified optical constants is small.…”
Section: Reflectance Modeling At 1310 Nmmentioning
confidence: 64%
See 2 more Smart Citations
“…The real part is that of Warren and Brandt (2008). For the imaginary part, Gosse et al (1995) recommend 4.26×10 −4 at −22 • C, with an error of 3% and a temperature dependence of 0.6% K −1 (Warren and Brandt, 2008), so that our value is within the acceptable range. The effect of using modified optical constants is small.…”
Section: Reflectance Modeling At 1310 Nmmentioning
confidence: 64%
“…Snow grain size has long been used as a substitute for SSA (Gow, 1969), but given the variety of grain shapes, from dendritic to rounded to hollow, the definition of grain size is ambiguous and observer-dependent (Aoki et al, 2000). With the example of hollow depth hoar crystals, Taillandier et al (2007) have shown that effective grain size deduced from SSA (Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrotron radiation produces Xray beams which are highly collimated and have orders of magnitude higher intensities than those from bench-top devices. This approach is particularly adapted to the study of the snow pack microstructure, because it gives µm voxel resolution images in a much shorter scanning time Flin et al, 2003;Flin and Brzoska, 2008). The aim of this study was to set up a technique to enable such a highresolution synchrotron-based tomography of tiny (sub-mm) graupel particles.…”
Section: F Enzmann Et Al: 3-d Imaging and Quantification Of Graupelmentioning
confidence: 99%
“…After segmenting the data into snow and pores, a method to measure local curvature from snow surface normal vectors and porosity medial axis was developed [13]. This technique has been further developed by Flin et al [14] and explored using µXRT data to study curvature evolution over time and to model grain growth and the sintering process [15].…”
Section: Introductionmentioning
confidence: 99%